Environmental Security in ASEAN: Challenge and Respond - Purwaning Putri Utami (2012)
Environmental security in Southeast Asia become important thing as the development of the region depends on the natural resources. As the consequences of the development, Southeast Asia region face several environmental degradation which may harm the ecosystem within the region. ASEAN as the regional institution within Southeast Asia region become the platform for the member states to overcome the environmental degradation. Several projects and programs are held in order to achieve the objectives. This paper project is focused on the environmental degradation within Southeast Asia and also the projects and programs under ASEAN on the environmental protection. In the other hand, the obstacles on the environmental cooperation will be discussed using the case of deforestation in Indonesia.